Video content delivery for the ESL classroom with vodcasting technology - Schalow, Thomas (Faculty of Communication and Modern Languages, Universiti Utara Malaysia, 2007)
In this paper I will explain the means by which video content can be delivered to the ESL classroom via a technology known as vodcasting. The ability to deliver video to the ESL classroom CAN profoundly change the learning process, and I will explore the implications of this new technology in this paper. It must be emphasized, however, that the ABILITY to deliver video does not NECESSARILY enhance the learning experience. Content material needs to be appropriate and delivered in a manner that leads toward mastery of required language skills. To meet that goal, I will explain how material can be organized into “knowledge units”, as defined by B.F. Skinner in his work on programmed learning techniques. Using these knowledge units we will progress beyond the linguistic competence emphasized in traditional classrooms and work toward achieving true communicative competence. The American psychologist B.F. Skinner believed people are best able to learn when the cognitive domain, or target material, is divided into knowledge units he called “learning frames”. He defined a learning frame as a limited set of new facts coupled with an incomplete statement or question the learner was required to complete based on information provided from within the frame itself, or from previous frames. Skinner’s “programmed learning” approach required that frames be ordered so that knowledge units required for subsequent frames were mastered before they were needed. Learning was made possible through a series of very small and rigidly ordered steps directed toward mastery of a series of learning frames and the inferences that could be associated with the facts contained within those learning frames. The step-by-step approach advocated by Skinner provided reinforcement for correct responses, and kept the student focused on the material being studied. Skinner was especially critical of traditional education’s inability to provide sufficient reinforcement for the material being studied. “Perhaps,” said Skinner, “the most serious criticism of the current classroom is the relative infrequency of reinforcement.” (Skinner, 1962, page 25) Skinner believed reinforcement was crucial to the learning process because it was only through repetition and reinforcement that a behavior, or acquired skill, could be maintained in strength. Skills not used frequently were easily lost, as language teachers and students can attest to. The concept of programmed learning based on learning frames and the sequential mastery of material became extremely influential in textbook development in the 1960s, even 3 though the practice of computerized programmed learning itself was limited by access to the rather expensive computers of the time. Ironically, interest in programmed learning techniques seemed to have waned just as the development of personal computers made it truly possible to implement the practices Skinner had advocated.